2009
DOI: 10.1111/j.1399-6576.2009.01965.x
|View full text |Cite
|
Sign up to set email alerts
|

Continuous femoral nerve block after total knee arthroplasty?

Abstract: A continuous femoral nerve block leads to better analgesia, less morphine consumption and less morphine-related side effects after TKA. Early functional recovery is improved, resulting in more patients reaching 90 degrees knee flexion after 6 days. However, after 3 months, no significant functional benefits were found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 19 publications
0
64
1
Order By: Relevance
“…Regional anesthesia is a well-established technique for total knee arthroplasty to provide a bridge to early postoperative analgesia, reduce opioid consumption, and improve mobility and rehabilitation. 3,4 The most widely used techniques are femoral nerve block (FNB), with or without sciatic nerve block (SNB), together with intrathecal anesthesia. 5 Several strategies involving regional anesthesia for joint arthroplasty have been designed to contain the cost of the surgery and secondary treatments and to decrease the economic burden on the health care system.…”
Section: Résumémentioning
confidence: 99%
“…Regional anesthesia is a well-established technique for total knee arthroplasty to provide a bridge to early postoperative analgesia, reduce opioid consumption, and improve mobility and rehabilitation. 3,4 The most widely used techniques are femoral nerve block (FNB), with or without sciatic nerve block (SNB), together with intrathecal anesthesia. 5 Several strategies involving regional anesthesia for joint arthroplasty have been designed to contain the cost of the surgery and secondary treatments and to decrease the economic burden on the health care system.…”
Section: Résumémentioning
confidence: 99%
“…Various studies have demonstrated the effectiveness of femoral nerve blocks in reducing pain post-total knee arthroplasty compared with intravenous PCA (3,7,8,(11)(12)(13)(14)(15)(16)(17). A systematic review of 112 studies between 1996 and 2005 by the PROSPECT working group supports the use of femoral nerve blocks for postoperative analgesia for primary TKA, based on the reduction in pain scores and supplemental analgesia (10).…”
Section: Discussionmentioning
confidence: 99%
“…We also requested additional data for three studies (Kadic 2009;Nader 2012;Wu 2014). Kadic 2009 gave the knee flexion results only as mean (range) and reported only the components of the WOMAC score but not the global score.…”
Section: Incomplete and Raw Datamentioning
confidence: 99%
“…Design: Three of the six studies were only single-blinded (Kadic 2009;Tammachote 2013;Zhang 2011), while three were unblinded (Nader 2012;Singelyn 1998;Wu 2014). Due to the nature of the interventions and their obvious numbing effect (participants received either a continuous femoral nerve block, an epidural catheter, or no regional technique), blinding of participants or personnel would have been difficult.…”
Section: Incomplete and Raw Datamentioning
confidence: 99%
See 1 more Smart Citation